The Complex of p-Tyr42 RhoA and p-p65/RelA in Response to LPS Regulates the Expression of Phosphoglycerate Kinase 1 - Oyungerel Dogsom; Amir Hamza; Shohel Mahmud; Jung-Ki Min; Yoon-Beom Lee; Jae-Bong Park (MDPI AG, 2023)
Inflammation plays a crucial role in tumorigenesis, primarily mediated by NF-κB. RhoA GTPases are instrumental in regulating the activation of NF-κB. Specifically, the phosphorylation of Tyrosine 42 on RhoA ensures the activation of NF-κB by directly activating the IKKβ associated with IKKγ (NEMO). This study aimed to uncover the molecular mechanism through which p-Tyrosine 42 RhoA, in conjunction with NF-κB, promotes tumorigenesis. Notably, we observed that p-Tyrosine 42 RhoA co-immunoprecipitated with the p-Ser 536 p65/RelA subunit in NF-κB in response to LPS. Moreover, both p-Tyrosine 42 RhoA and p-p65/RelA translocated to the nucleus, where they formed a protein complex associated with the promoter of phosphoglycerate kinase 1 (PGK1) and regulated the expression of PGK1. In addition, p-p65/RelA and p-Tyr42 RhoA co-immunoprecipitated with p300 histone acetyltransferase. Intriguingly, PGK1 exhibited an interaction with β-catenin, PKM1 and PKM2. Of particular interest, si-PGK1 led to a reduction in the levels of β-catenin and phosphorylated pyruvate dehydrogenase A1 (p-PDHA1). We also found that PGK1 phosphorylated β-catenin at the Thr551 and Ser552 residues. These findings discovered that PGK1 may play a role in transcriptional regulation, alongside other transcription factors.